Influenza vaccination for all pregnant women? So far the less biased evidence does not favour it - Alberto Donzelli (Human Vaccines & Immunotherapeutics, 2019)
Pregnant women are a WHO priority group for influenza vaccination, but evidence from observational studies in pregnancy is subject, among others, to the healthy-vaccinee bias, overestimating the vaccine effectiveness and safety. An USA survey adds new evidence that documents this bias. Therefore, it is essential to assess vaccine effectiveness and safety with RCTs. Cochrane reviews identified one RCT with “low risk of bias”, in a medium-income country, with NNV 55 for mothers. Its data show an excess of local adverse effects, and a tendency to harm for serious adverse events, with uncertain or very limited protection against influenza. A subsequent larger trial in a very-low-income African country found an excess of infant serious infections plus deaths in the influenza vaccine group. Also an available previous small trial and a subsequent large one in Asian low-income countries showed in tendency more deaths in the offspring vaccine groups. Before promoting seasonal influenza vaccinations during all pregnancies, more independent trials are needed, with appropriate designs and comparators. Meanwhile, vaccination in second-third trimester could be offered communicating the uncertainties and promoting informed choices, without neglecting to promote other protective behaviors.